2013
DOI: 10.1002/pip.2419
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial study of NaF addition in CIGSe films for high efficiency solar cells

Abstract: We report on a sodium fluoride (NaF) thickness variation study for the H2Se batch furnace selenization of sputtered Cu(In,Ga) films in a wide range of Cu(In,Ga) film compositions to form Cu(In,Ga)Se2 (CIGSe) films and solar cells. Literature review indicates lack of consensus on the mechanisms involved in Na altering CIGSe film properties. In this work, for sputtered and batch‐selenized CIGSe, NaF addition results in reduced gallium content and an increase in grain size for the top portion of the CIGSe film, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 55 publications
(129 reference statements)
3
31
0
Order By: Relevance
“…Such HTE research has been performed for a range of solar cell absorber materials, from quite mature (e.g., Cu(In,Ga)Se 2 , 40 ). For some of these absorbers, the PV efficiency was correlated with quasi-Fermi level splitting determined from photoluminescence mapping.…”
Section: Opportunities Energy Generation: Photovoltaicsmentioning
confidence: 99%
“…Such HTE research has been performed for a range of solar cell absorber materials, from quite mature (e.g., Cu(In,Ga)Se 2 , 40 ). For some of these absorbers, the PV efficiency was correlated with quasi-Fermi level splitting determined from photoluminescence mapping.…”
Section: Opportunities Energy Generation: Photovoltaicsmentioning
confidence: 99%
“…Selenisation was performed at 250 °C for 60 min followed by 1-5 min at 500 °C, giving the composition range of Cu/(In+Ga)=0.8-1 and Ga/(In+Ga)=0.30-0.45. All detailed preparations and characterizations of CIGS layers have been previously reported [11]. Eid et al [11] demonstrated that the thickness of added NaF to the CIGS layers changes the efficiency of solar cells: increasing NaF thickness from 0 to 15 nm increased solar cell efficiencies from <10% to 16.0% (without antireflective coatings), but increasing NaF thickness from 15 to 30 nm decreased solar cell efficiencies.…”
Section: Cigs Thin-film Preparationmentioning
confidence: 99%
“…All detailed preparations and characterizations of CIGS layers have been previously reported [11]. Eid et al [11] demonstrated that the thickness of added NaF to the CIGS layers changes the efficiency of solar cells: increasing NaF thickness from 0 to 15 nm increased solar cell efficiencies from <10% to 16.0% (without antireflective coatings), but increasing NaF thickness from 15 to 30 nm decreased solar cell efficiencies. Here, CIGS layers grown with 0-, 10-, 15-, 20-, or 30-nm NaF (CIGS-0NaF, CIGS-10nmNaF, CIGS-15nmNaF, CIGS-20nmNaF, CIGS-30nmNaF, respectively) were chosen in our time-resolved spectroscopic study.…”
Section: Cigs Thin-film Preparationmentioning
confidence: 99%
See 2 more Smart Citations